2017
DOI: 10.1016/j.cobeha.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex GABAergic deficits and circuit dysfunction in the pathophysiology and treatment of chronic stress and depression

Abstract: Psychiatric diseases, notably major depression, are associated with imbalance of excitatory and inhibitory neurotransmission within the prefrontal cortex (PFC) and related limbic brain circuitry. In many cases these illnesses are precipitated or exacerbated by chronic stress, which also alters excitatory and inhibitory neurotransmitter systems. Notably, exposure to repeated uncontrollable stress causes persistent changes in the synaptic integrity and function of the principal glutamatergic excitatory neurons i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(113 citation statements)
references
References 63 publications
5
108
0
Order By: Relevance
“…Notably, regarding the differential phosphorylation changes induced by ketamine, but not by CUMS, ''synapse'' still accounts for a large proportion of the categories from the GO analysis (Figures 5B,E). Consistent with our study, many previous studies have shown that ketamine can reverse the synaptic deficits caused by stress (Li et al, 2011;Belujon and Grace, 2014;Ghosal et al, 2017). Surprisingly, only a few phosphorylation sites were overlapping between the mPFC and the NAc induced by CUMS and ketamine, respectively (Supplementary Figure S5).…”
Section: Discussionsupporting
confidence: 92%
“…Notably, regarding the differential phosphorylation changes induced by ketamine, but not by CUMS, ''synapse'' still accounts for a large proportion of the categories from the GO analysis (Figures 5B,E). Consistent with our study, many previous studies have shown that ketamine can reverse the synaptic deficits caused by stress (Li et al, 2011;Belujon and Grace, 2014;Ghosal et al, 2017). Surprisingly, only a few phosphorylation sites were overlapping between the mPFC and the NAc induced by CUMS and ketamine, respectively (Supplementary Figure S5).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it will allow the optogenetic and/or CRE-line targeting of very specific neurons for the purposes of investigation (Bernard, Sorensen, & Lein, 2009;Cardin et al, 2010) and treatment (Hunt et al, 2013;Ghosal, Hare, & Duman, 2017;Chohan & Moore, 2016). Precision is especially important in translational research, and understanding the role of particular neurons in normal and diseased functioning requires a cumulative knowledge incorporating morphology, electrophysiology, and molecular expression profiles (Seung & Sümbül, 2014;Cadwell et al, 2016;Armananzas & Ascoli, 2015;PING, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from clinical trials indicated that GABAergic neurotransmission and GABA content were substantially decreased in depressed patients . Additionally, GABAergic interneuron is a leading cause of alteration in depressed patients and is beneficial to the increased of self‐focus and cogitation in depressive patients . Our previous electrophysiological study showed that inhibitory synaptic transmission was down‐regulated in NAc GABAergic neurons in the depression model .…”
Section: Introductionmentioning
confidence: 91%
“…[6][7][8] Additionally, GABAergic interneuron is a leading cause of alteration in depressed patients and is beneficial to the increased of self-focus and cogitation in depressive patients. 9,10 Our previous electrophysiological study showed that inhibitory synaptic transmission was down-regulated in NAc GABAergic neurons in the depression model. 11 The lower GABA content from presynaptic terminals in the NAc tissue may be conferred to the aetiology of chronic unpredictable mild stress (CUMS)-induced depression.…”
Section: Introductionmentioning
confidence: 99%